THE GRAMMATICAL SHIFT IN TRANSLATING CAUSATIVE CONSTRUCTION FROM INDONESIAN INTO ENGLISH IN ANDREA HIRATA’S NOVEL “LASKAR PELANGI AND THE RAINBOW TROOPS” - Cucu Mariam; Lungguh Halira Vonti (UNIVERSITAS PAKUAN, 2020)
The purpose of this study is to find causative construction in Indonesian and English in the novel Laskar Pelangi and the translation of The Rainbow Troops by Andrea Hirata, analyse and examine in depth the equivalence and grammatical incompatibility of the translation of the causative construction, and describe the shift in grammatical equivalence of the translation of causative constructs from Indonesian into English. The method used in this study is content analysis with a qualitative approach. This method is used to find facts about grammatical equivalence in the form of causative construction. The shift in the word level occurs at a higher level, namely the phrase, at the phrase level there is no shift, and at the level of the clause, there is a shift at a lower level, namely the phrase or higher level, namely the main clause and sentence. In the sentence level, the shift occurs in the type of sentence, into sentences that are wider or smaller, or into clauses. The novelty in this research is the grammatical equivalence of causative constructs in translation and its shift from Indonesian into English.